EnviroCircuit - Muijs, Rik (My University, 2023)
This thesis explores how to design immersive virtual reality (VR) racing experiences for different levels of player experience. The thesis follows an iterative design process that involves discovering, designing, prototyping, and evaluating three different VR racing prototypes. The thesis presents a set of guidelines for designing immersive VR racing experiences and a functional prototype. The guidelines can be considered by future researchers and designers when wanting to develop immersive racing experiences, and as a result make these experiences more easily accessible for people with various amounts of experience with virtual racing.
Keywords: Racing; Immersion; VR; Interaction Design; Game Design; Video Game; Immersive Experience